Pengaruh Return On Asset, Debt To Asset Ratio dan Current Ratio Terhadap Financial Distress pada Perbankan - Monica Febriyanti; Budi Kurniawan (UNIVERSITAS KALBIS, 2022)
The purpose of this study was to see the return on assets, debt to assets ratio, and current ratio to financial distress. Financial distress can be done by all companies, both large and small companies. In this study, the method used is quantitative research, with research methods using literature review from scientific journals. This study shows the results that show that the return on assets to financial distress, debt to asset ratio has an effect on financial distress, and the current ratio has no effect on financial distress.